2016
DOI: 10.1111/jdi.12572
|View full text |Cite
|
Sign up to set email alerts
|

Vildagliptin reduces plasma stromal cell‐derived factor‐1α in patients with type 2 diabetes compared with glimepiride

Abstract: Aims/IntroductionDipeptidyl peptidase‐4 inhibitors might have pleiotropic protective effects on cardiovascular disease (CVD), in contrast to sulfonylureas. Therefore, we compared various CVD risk factors between vildagliptin and glimepiride.Materials and MethodsWe carried out a randomized, prospective and crossover trial. A total of 16 patients with type 2 diabetes whose glycated hemoglobin was >7% were randomized to add vildagliptin or glimepiride. After 12‐week treatment, each drug was replaced with the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
5
13
1
Order By: Relevance
“…In two recent studies, vildalgliptin treatment significantly reduced (C-term) SDF-1α plasma levels [20,21]. At variance with our results, Aso et al [22] found that sitagliptin decreased SDF-1a levels compared with glimepiride.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In two recent studies, vildalgliptin treatment significantly reduced (C-term) SDF-1α plasma levels [20,21]. At variance with our results, Aso et al [22] found that sitagliptin decreased SDF-1a levels compared with glimepiride.…”
Section: Discussioncontrasting
confidence: 51%
“…This study has shown that sitagliptin therapy has a favourable effect on SDF-1α levels. Of note, various effects of DPP-4 therapy on SDF-1α levels have hitherto been reported [15][16][17][18][19][20][21][22]. A small clinical trial showed that sitagliptin therapy significantly increased EPCs and SDF-1α [9].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, plasma SDF-1α decreased with the effect of vildagliptin, which seems to be a converse effect of DPP-4 inhibitors on SDF-1α. Although the reason is unclear, this finding is consistent with a previous report [ 14 ] and may occur only with vildagliptin. The minimum level of plasma SDF-1α is on day 2, which is consistent with the pharmacokinetics of vildagliptin that the estimated volume of distribution is high (71 L) and that the fraction bound to proteins is relatively low (9.3%).…”
Section: Discussionsupporting
confidence: 92%
“…In the Framingham Heart Study of 3359 participants (10% of individuals with diabetes), high plasma SDF-1α were directly and independently associated with the risk of heart failure and 10-year all-cause mortality [56]. Two independent randomized double-blind control studies [14,32] in small groups of DM2 patients provide interesting evidence for the effect of vildagliptin on SDF-1α. Although DPP-4 degrades SDF-1α and its blockade should be associated with an increase in SDF-1α, the administration of vildagliptin resulted in a significant decrease in circulating SDF-1α.…”
Section: Vascular Endotheliummentioning
confidence: 99%